1999
DOI: 10.1136/thx.54.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Addition of salmeterol versus doubling the dose of fluticasone propionate in patients with mild to moderate asthma

Abstract: Background-The objective of this multicentre, randomised, double blind, parallel group study was to compare the eYcacy and safety of the addition of salmeterol with that of doubling the dose of fluticasone propionate in asthmatic patients not controlled by a low or intermediate dose of inhaled corticosteroids. Methods-After a four week run in period of treatment with fluticasone propionate (100 µg twice daily if pre-trial dose was 400-600 µg inhaled corticosteroids or 250 µg twice daily if pre-trial dose was 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 19 publications
3
51
0
2
Order By: Relevance
“…The fixed combination is at least as effective as both of its components are individually and has the advantage that only one inhaler has to be used by the patient, which is expected, although not proven, to increase adherence to therapy [38]. Furthermore, it has been indicated that addition of a long-acting b 2 -adreoceptor agonist to an inhaled steroid provides greater clinical advantage than doubling the dose of inhaled steroids in patients with symptomatic asthma [36,42]. The combination of both drugs in one inhaler influences neither the pharmacodynamic and pharmacokinetic characteristics nor the side-effect profiles of the individual substances [40].…”
Section: Combining Glucocorticoids and B 2 -Adrenoceptor Agonistsmentioning
confidence: 99%
“…The fixed combination is at least as effective as both of its components are individually and has the advantage that only one inhaler has to be used by the patient, which is expected, although not proven, to increase adherence to therapy [38]. Furthermore, it has been indicated that addition of a long-acting b 2 -adreoceptor agonist to an inhaled steroid provides greater clinical advantage than doubling the dose of inhaled steroids in patients with symptomatic asthma [36,42]. The combination of both drugs in one inhaler influences neither the pharmacodynamic and pharmacokinetic characteristics nor the side-effect profiles of the individual substances [40].…”
Section: Combining Glucocorticoids and B 2 -Adrenoceptor Agonistsmentioning
confidence: 99%
“…Inhaled corticosteroids and LABAs can be administered in combination to obtain additive clinical benefits, and there are also molecular interactions between these drugs that can lead to synergistic effects [3]. In asthmatic patients, LABA/ICS combinations produce greater improvements in lung function, symptom control and exacerbation rate reduction compared with doubling the dose of ICS [4][5][6][7][8]. Unfortunately, despite the widespread availability of these combination therapies, many patients with asthma remain poorly controlled [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although increasing the dose of ICS can be a treatment option, the local and systemic adverse effects of high-dose ICS make this alternative less valuable [3, 4]. Therefore, the addition of a second treatment with a supplementary effect mechanism enables better asthma control [1, 2, 5, 6, 7, 8]. Recent studies have also supported the use of long-acting β 2 agonists and ICS together [6, 7, 8, 9, 10, 11].…”
Section: Introductionmentioning
confidence: 99%